Synthesis and pairing properties of oligonucleotides containing 3-hydroxy-4-hydroxymethyl-1-cyclohexanyl nucleosides - Maurinsh, Y; Rosemeyer, H; Esnouf, R; Medvedovici, A; Wang, J; Ceulemans, G; Lescrinier, E; Hendrix, C; Busson, R; Sandra, P; Seela, F; Van Aerschot, A; et al. (1999)
The enantiomeric forms of cyclohexanyl adenine and thymine nucleosides were obtained by separation of their diastereomeric esters with (R)-(-)-methylmandelic acid. The four nucleoside analogues were appropriately protected, converted to their phosphoramidites and oligomerized. The resulting cyclohexanyl nucleic acids (CNAs) represent a new enantioselective Watson-Crick base-pairing system. Homochiral oligomers of equivalent chirality show Watson-Crick pairing, while those of opposite chirality (D-CNA and L-CNA) do not. No isochiral or heterochiral adenine-adenine or thymine-thymine base pairing is observed. Complex formation occurs only between oligomers in antiparallel orientations. D-CNA hybridizes with natural nucleic acids, and the strength of the interaction decreases in the order dsCNA 〉 CNA:RNA 〉 CNA:DNA. Thus, the D-cyclohexanyl nucleic acids are RNA-selective. L-CNA hybridizes either very weakly or not at all with natural nucleic acids, and the nature of this association is not clear. This study of CNAs leads us to hypothesize that a) the conformation of a single nucleoside analogue may be different from its conformation in an oligonucleotide and b) the conformational stress of a nucleotide analogue incorporated in an oligomer may contribute to the sequence-dependent thermal stability of oligonucleotide complexes.